Up to half of companies would be behind on their climate targets under stricter scope 2 accounting rules - Anders Bjørn; Jens Friis Lund; Matthew Brander (Environmental Research Letters)
Companies have been accused of overstating their scope 2 emission reductions through purchases of ineffective renewable energy certificates (RECs). Therefore, several actors have proposed stricter accounting rules targeting additionality and deliverability. In this paper we explore how such restrictions would quantitatively affect the scope 2 emissions and target progress reported by companies. We consider three accounting restrictions: geographical proximity, facility age, and power purchase agreement. The study involves adjusting the market-based scope 2 emissions reported by 206 companies based on the portion of their purchased RECs that would become invalid under the proposed accounting restrictions. We find that the sample companies have more than doubled their purchases of RECs between their base year (typically 2019) and 2022, including an increase in RECs that would be invalid under the proposed accounting restrictions. The introduction of all three accounting restrictions would entail that the combined scope 2 emission reduction reported by the sample companies falls from 21% to 17%. Similarly, the share of sample companies that were behind on their climate target in 2022 would increase from 28% to 50% under all three accounting restrictions. However, a small subset of the company sample has over time replaced potentially invalid RECs with valid RECs, and the accounting restrictions would lead to improved target performance for these companies. Our findings can inform the revision of the greenhouse gas protocol and emerging accounting standards around renewable fuels.